Does credit constraint matter for technical efficiency, technological shifts, and profitability of flower growers? An empirical study - Sandip Mitra; Md. Rashid Asef Dipto; Yasin Ibrahim Ankon (Cogent Economics & Finance, 2024)
This study aims to investigate the variations in efficiency, technology gap, and profitability of flower producers depending on their credit constraint position. A total of 160 flower farmers have been selected from Bangladesh by using a multistage sampling technique. Meta-frontier Data Envelopment Analysis (DEA) is employed to estimate the efficiency differences and technological gaps depending on the credit constraint situation. At the same time, the Tobit regression model is used to estimate the factors influencing the meta-technical efficiency of flower farmers. Profitability differences depending on the credit constraint situation are identified using the gross margin and benefit cost ratio. The mean meta-technical efficiency for Marigold farmers is highest when unconstrained (0.73) and lowest when credit is constrained (0.64) relative to the meta-frontier, which indicates output could be increased by 27 and 36%, respectively, without increasing input. On the other side, the efficiency of credit-unconstrained rose farmers is slightly higher than that of constrained rose farmers. In addition, credit-constrained marigold farmers achieve the lowest technological gap ratio (0.64) compared to credit-unconstrained farmers. Sociodemographic and farm characteristics such as education, source of seed, land tenure, farm area, and age have a significant positive impact, while earning family members, types of flowers, and credit constraints have a significant negative effect on the technical efficiency of flower farmers. The profitability of credit-unconstrained marigold and rose farmers is higher than that of credit-constrained farmers. Facilitating the loan application process, easing the pre-conditions of loan acceptance, and adjusting the repayment schedule help to remove the credit-constrained situation. Bangladesh's floriculture industry has significant potential, but small-scale farmers face challenges due to limited access to credit. High interest rates and strict collateral requirements hinder their ability to improve technical efficiency, technological gap, and profitability. This study addresses the often-overlooked impact of credit constraints on flower farmers' efficiency, technological gap, and profitability. Farmers with access to credit are more efficient, as timely investment in inputs increases productivity and profitability. In contrast, limited credit access hampers input application, reducing both productivity and technical efficiency, trapping farmers in low-profit cycles, and increasing the technological gap. Researchers interested in the financial constraints in agriculture and their effect on productivity, efficiency, and profitability can gain valuable insights from this study. It also emphasizes the need for policymakers to enhance access to affordable credit by lowering interest rates and easing collateral requirements, which will help boost productivity and support the sustainable growth of Bangladesh's floriculture sector.
Keywords: 330; profitability; technical efficiency; Credit constraint; flower; technological gap